EFFECTIVENESS OF THE ROLE OF LEADERS ON STUDENT ORGANIZATIONAL PERFORMANCE (EMPIRICAL STUDY OF ORMAWAS FEB UNWAHAS PERIOD 2021/2022) - Siti Umi Sa'adatur Rohmah; Fatkhur Rohim; Saiful Bahri (International Journal of Management, Business, and Social Sciences, 2023)
There is a difference between the theory of leaders and the reality of organizational conditions. In one of the student organizations the Faculty of Economics and Business has not been able to influence members to carry out their duties. And it's different from the other 4 institutions where leaders can influence members to carry out their duties properly. The leader has been able to carry out the theory of the leader as a director and influence so that members can carry out their duties following the responsibilities that have been given. The type of research used in this research is qualitative research, the qualitative research used is descriptive. And the location of the research conducted was at the Faculty of Economics and Business, Wahid Hasyim University, Semarang. From the results of the research findings, in general, the leaders at Ormawa FEB have carried out their responsibilities well. Judging from the role of the leader as a planner, the leader can plan and make decisions carefully. Leaders also have good morale that can influence their members. Communication at Ormawa FEB is quite good but not optimal, and the leader's work performance is good with the embodiment of excellent work programs at several institutions in the student organization of the Faculty of Economics and Business, Wahid Hasyim University Semarang for the 2021/2022 period.